2017
DOI: 10.1002/smll.201702909
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Stability and Immunomodulatory Activity of Liposomal Spherical Nucleic Acids through Lipid‐Tail DNA Modifications

Abstract: Liposomal spherical nucleic acids (LSNAs) are an attractive therapeutic platform for gene regulation and immunomodulation due to their biocompatibility, chemically tunable structures, and ability to enter cells rapidly without the need for ancillary transfection agents. Such structures consist of small (<100 nm) liposomal cores functionalized with a dense, highly oriented nucleic acid shell, both of which are key components in facilitating their biological activity. Here, the properties of LSNAs synthesized us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(85 citation statements)
references
References 57 publications
0
85
0
Order By: Relevance
“…The release profiles of the nucleic acid shell for all three PLGA‐SNAs are similar, exhibiting half‐lives of more than 2 h with K obs ranging from 7.4 × 10 −5 to 8.8 × 10 −5 s −1 (Figure C, Table ). These K obs values suggest that PLGA‐SNAs are nearly 100‐fold more stable than the most clinically advanced liposomal SNAs and three times more stable than the lipid‐tail SNAs ( K obs = 7.9 × 10 −3 s −1 and 2.8 × 10 −4 s −1 for liposomal SNA and lipid‐tail LSNAs, respectively) . The increased stability of the PLGA‐SNAs are likely due to the covalent bond utilized to immobilize the nucleic acids on the NPs and the intrinsically higher stability of polymer NPs (as compared with liposomes).…”
Section: Methodsmentioning
confidence: 96%
“…The release profiles of the nucleic acid shell for all three PLGA‐SNAs are similar, exhibiting half‐lives of more than 2 h with K obs ranging from 7.4 × 10 −5 to 8.8 × 10 −5 s −1 (Figure C, Table ). These K obs values suggest that PLGA‐SNAs are nearly 100‐fold more stable than the most clinically advanced liposomal SNAs and three times more stable than the lipid‐tail SNAs ( K obs = 7.9 × 10 −3 s −1 and 2.8 × 10 −4 s −1 for liposomal SNA and lipid‐tail LSNAs, respectively) . The increased stability of the PLGA‐SNAs are likely due to the covalent bond utilized to immobilize the nucleic acids on the NPs and the intrinsically higher stability of polymer NPs (as compared with liposomes).…”
Section: Methodsmentioning
confidence: 96%
“…The structural features of SNA H that drive the enhancement of codelivery are (i) the linkage of antigen to CpG by chemical conjugation and nucleic acid hybridization and (ii) the enhancement of cellular uptake of oligonucleotides by the SNA architecture. SNA H is not susceptible to erosion in codelivery through the mechanisms likely responsible for the separation of antigen and CpG in SNAs E and A (i.e., leakage of peptide through liposome membranes, desorption of antigen-functionalized oligonucleotides from liposomes) (30).…”
Section: Codelivery Of Immunostimulatory Oligonucleotides and Peptidementioning
confidence: 99%
“…Serum stability is another structural parameter of cellular uptake. In 2018, Meckes et al prepared two versions of liposome‐cored SNAs by anchoring DNA oligonucleotides to the lipid bilayer via cholsterol molecules or hexadecyl chains . By using a Förster resonance energy transfer (FRET)‐based assay, the authors showed that hexadecyl‐based SNAs have a >20‐fold longer half‐life in serum‐containing medium than cholesterol‐based SNAs, with dissociation rates of 2.8 × 10 −4 and 7.9 × 10 −3 s −1 , respectively.…”
Section: Governing Factors Of the Cellular Uptake Of Dna Nanostructuresmentioning
confidence: 99%